2018
DOI: 10.1242/jcs.219063
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of the signaling pathway required for the cell wall integrity checkpoint

Abstract: The cell wall integrity checkpoint monitors synthesis of cell wall materials during the cell cycle. Upon perturbation of cell wall synthesis, the cell wall integrity checkpoint is activated, downregulating Clb2 transcription. Here, we identified genes involved in this checkpoint by genetic screening of deletion mutants. In addition to the previously identified dynactin complex, the Las17 complex, in particular the Bzz1 and Vrp1 components, plays a role in this checkpoint. We also revealed that the high osmolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Under cell wall stress, SakA also physically interacts with the CWI MAPK, MpkA, and the PtcB MAPK phosphatase, suggesting a close connection between the HOG and CWI pathways. Cross-talk between the HOG and CWI pathways has been observed in several fungal species, including S. cerevisiae, Candida albicans, Fusarium graminearum, and Pyrenophora graminea (56)(57)(58)(59)(60)(61)(62)(63)(64). Now, we show that the absence of these two HOG pathwayassociated MAPKs, MpkC and SakA, abolishes the remodeling of the phosphoproteome seen in the wild-type fungus in response to cell wall damage, and we also reveal novel proteins potentially involved in cell wall stress response.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Under cell wall stress, SakA also physically interacts with the CWI MAPK, MpkA, and the PtcB MAPK phosphatase, suggesting a close connection between the HOG and CWI pathways. Cross-talk between the HOG and CWI pathways has been observed in several fungal species, including S. cerevisiae, Candida albicans, Fusarium graminearum, and Pyrenophora graminea (56)(57)(58)(59)(60)(61)(62)(63)(64). Now, we show that the absence of these two HOG pathwayassociated MAPKs, MpkC and SakA, abolishes the remodeling of the phosphoproteome seen in the wild-type fungus in response to cell wall damage, and we also reveal novel proteins potentially involved in cell wall stress response.…”
Section: Discussionsupporting
confidence: 54%
“…It is possible that A. fumigatus AsgA is similarly involved in some aspects of the cell wall damage response. In S. cerevisiae, the forkhead family transcription factor Fkh2 is involved in the activation of early-firing replication (68) and Fkh2 mutations suppress the checkpoint-defective phenotype of both HOG and cell wall integrity MAPK mutations (63). Therefore, the A. fumigatus homologue, FkhA, could be a putative CWI checkpoint for cell cycle progression in A. fumigatus.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in the absence of Slt2, Hcm1 is partially stabilized, similar to that observed in the nonphosphorylatable Hcm1 mutant [64]. All these observations have led to the suggestion that MAPK Slt2 triggers Hcm1 degradation by phosphorylation at Ser 61 , Ser 65 , and Ser 66 in response to cell-wall damage, eventually inducing the blockage of cell-cycle progression in G2/M. Supporting this, more recently, it has been reported that mutant strains in all components of the MAPK cascade are defective in blocking cell-cycle progression, as deduced from the presence of SPB separation under cell-wall stress conditions [65].…”
Section: The Cwi (Cell-wall Integrity) Checkpointmentioning
confidence: 52%
“…When the CWI checkpoint is triggered by cell-wall damage, the cellular levels of Hcm1 drop dramatically. This regulation occurs through a post-transcriptional mechanism involving the phosphorylation of at least Ser 61 , Ser 65 , and Ser 66 , which likely destabilizes the protein. As a consequence, the transcription of many genes regulated by Hcm1 (including the FKH2 and NDD1 genes) is impaired.…”
Section: The Cwi (Cell-wall Integrity) Checkpointmentioning
confidence: 99%
See 1 more Smart Citation